Technological Change and the Demand for Skills in the 1980s: Does Skill Mismatch Explain the Growth of Low Earnings? - David R. Howell (Levy Economics Institute of Bard College, 1993)
The earnings of low-skill workers have suffered substantial declines since the mid 1970 s. The conventional explanation is that a technology-induced increase in skill requirements has resulted in a growing mismatch between the skills demanded by firms and those supplied by the workforce: declining demand for low-skill workers led to falling relative (and real) wages. But neither statistical nor case study evidence indicates that this period was characterized by a fundamental, economy-wide transformation in production technology or by a shift in the longterm upward trend in skill requirements whose timing and magnitude could account for the wage restructuring. What the evidence does suggest is that the collapse in wages was largely unrelated to skill restructuring. In the face of sharply increasing competition, employers adopted a low-road strategy aimed above all at reducing labor costs, through wage concessions from workers, the replacement of full-time with part-time and temporary workers, an increased reliance on low-wage outside contractors, and relocation to low-wage sites - a human resource strategy that was facilitated by rising supplies of workers willing to accept low wages (e.g., displaced high-wage workers and low-skill immigrants) and a variety of government policies. The mismatch appears to be less between skills demanded and skills supplied than between skills demanded and wages paid. This suggests that while there is a need to improve our education and training system, improving worker skills will not, by itself, have much impact on the distribution of earnings.
Keywords: 330